Ultrasound Treatment of Iota-Carrageenan and Guar Gum - Kseniya N. Nitsievskaya; Svetlana V. Stankevich; Elena V. Boroday (Техника и технология пищевых производств)
Hydrocolloids make it possible to produce low-calorie analogues of traditional foods that maintain the original structural properties. Electrophysical methods control viscosity and stabilize food systems. However, the stabilizing effect of ultrasonic treatment on gel remains understudied. The research featured the effect of ultrasonic treatment on hydrocolloids (polysaccharides) used in meat or fish jelly, marmalades, marshmallows, puddings, ice cream, etc. The study involved samples of colloidal systems based on iota-carrageenan or guar gum and purified water (1:100). The samples underwent ultrasonic treatment at various time and pH ranges. The viscosity, active acidity, temperature, and transparency (transmission coefficient, T, %) of the obtained colloidal systems were determined using standard methods, while the sensory profile was defined by the descriptor-profile method. Hydrocolloids were subjected to ultrasound at pH 3.9, 7.0, and 9.0. The colloidal viscosity of the iota-carrageenan sample was 47.6 mPa·s at neutral pH, 45.7 mPa·s at acidic pH, and 22.3 mPa·s at alkaline pH. The viscosity of the hydrocolloid system with guar gum depended on the pH of the medium: it decreased during processing from 119.0 to 64.8 mPa·s in the neutral medium but remained the same (3.5 ± 0.2 mPa·s) in the acid medium and reached 6.52 mPa·s in the alkaline medium. The maximum temperature of the colloidal system was 46.5°C in a neutral medium. The system with iota-carrageenan showed the best result at medium acidity in the range of 3.9–6.0 units and produced a fluid gel-like structure. Sonicated iota-carrageenan could be recommended as a gelling agent. Guar gum viscosity, on the contrary, lost its viscosity and failed to produce the desired structure.